Characteristics analysis of microRNAs in the interaction between maize and Ostrinia furnacalis - Zhang, Rui-Xue; Zhao, Xin; Liu, Na; Li, Rui-Huan; Yao, Jun-Jin; Xu, Chao; Qi, Xin; Zhang, Chen; Wang, Ya-Si; Lan, Qing-Kuo; Wang, Yong; Cheng, You-Pu; et al. (Frontiers in Ecology and Evolution, 2025)
To investigate the expression of micro RNAs (miRNA) at the transcriptome level in interactions between maize (Zea mays) and the Asian corn borer (Ostrinia furnacalis), four miRNA libraries were constructed based on four groups of samples: fresh, uneaten maize leaves; maize leaves eaten by Asian corn borer larvae; Asian corn borer larvae that had eaten maize leaves; and Asian corn borer reared on an artificial diet). Through second-generation sequencing technology, 810 known miRNAs and 132 new miRNAs were identified and analyzed. In specific miRNA comparisons, five new plant-derived miRNAs were found in the Asian corn borer larvae, of which one was differentially expressed because of its diet. Expression levels of all differentially expressed miRNAs were validated using qRT PCR. Because of biotic stress and differences in food types, miRNAs with cross-kingdom transfer were regulated by their target genes to express metabolic factors such as transcription factors (e.g., growth hormone response factors (ARF6, ARF8), inorganic phosphate transporters (Pht10), and phosphate transporters (Pht7, Pht9)). We improve understanding of the roles of microRNAs in plant–insect interactions, and establish a foundation upon which new maize varieties with resistance to Asian corn borer larvae can be developed through genetic engineering.